Institutionalization and autonomy of art: Can socially engaged art be institutionalized? - Trentini, Bruno (Labyrinth, 2020)
This paper deals with the autonomy of art and more specifically with the autonomy of socially engaged art once it is institutionalized. The originality of the article is its use of Goodman's terminology to theorize socially engaged art. By comparing two works of art from the same collective (one without an institutional framework and the other in a festival), the main issue is to defend the hypothesis that artistic consecration prevents an emancipatory action from functioning as art or prevents an action from functioning as socially engaged art. Thus, in the context of engaged art, the question is no longer "when is art?" but "where is art?".